Pendampingan Sumber Tanaman Pangan Obat ( Tanobat ) di Desa Cilimus Kecamatan Teluk Pandan Kabupaten Pesawaran Lampung - Nurmalia, Gustika; Bittaqwa, Bry Bima; Azizah, Novi Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The aim of the service is to provide socialization and implementation of the concept of combining food and medicinal plants in the context of stunting prevention and the use of traditional herbal ingredients. in Cilimus Village. The research method involves outreach and training activities for the community regarding the benefits and use of various plants, such as eggplant to prevent stunting, chilies to enrich dishes, and ginger as a herbal concoction. The results of the service show that Tanobat is able to have a positive impact, both in efforts to prevent stunting through the introduction of eggplant, and in the use of traditional herbal ingredients such as ginger. The people of Cilimus Village are increasingly aware of the added value of food and medicinal plants, and appreciate their traditional herbal heritage. The conclusion is that the introduction of the Tanobat concept can strengthen community empowerment by improving health and welfare through easily accessible food and medicinal plants, as well as maintaining valuable herbal traditions. This effort supports the goals of sustainable development and improving the quality of life of the community